Risk factors for brain damage among preterm twins. (16th February 2018) - Schushan-Eisen, Irit; Maayan-Metzger, Ayala; Mazkereth, Ram; Leibovitch, Leah; Strauss, Tzipora
Abstract: Aim: To evaluate the perinatal and postnatal risk factors for various brain pathologies among preterm twins. Methods: Retrospective data of 104 twin pairs of which one of the siblings had evidence of abnormal head ultrasound (HUS) and its co-twin with normal HUS served as control. Results: Abnormal HUS consisted of periventricular echodensities among 69 infants, intraventricular hemorrhage among 28 infants, cystic periventricular leukomalacia among 10 infants, and other parenchymal brain pathologies among 5 infants. Perinatal and postnatal complications were similar between study and controls. Siblings with severe brain pathologies were ventilated for longer time over their co-twins. In 10 out of 11 cases of discordant twins (≥20%) with severe brain pathology, the severe pathology was recorded in the larger sibling. Conclusions: Our study results, which included matched preterm twin pairs for study/control groups to evaluate risk factors for the overall evidence of brain injury, could not determine specific risk factors for these brain pathologies. The finding that severe brain pathologies were more common among the larger co-twin requires further study of and attention to short- and long-term outcomes and the potential conflicts that may arise.